Multiplex genetic cancer testing identifies pathogenic mutations in TP53 and CDH1 in a patient with bilateral breast and endometrial adenocarcinoma - Heitzer, Ellen (BioMed Central, 2013)
BACKGROUND: Germline genetic testing for familial cancer syndromes is usually performed serially for the most likely genetic causes. In recent years the way genetic testing carried out has changed, as next generation sequencing now allows the simultaneous testing of multiple susceptibility genes at low costs. CASE PRESENTATION: Here, we present a female with bilateral breast cancer and endometrial adenocarcinoma. After simultaneous sequencing of 150 genes (890 kb) associated with hereditary cancer we identified pathogenic mutations in two high-penetrance genes, i.e. TP53 and CDH1 that would most likely not have been elucidated by serial screening of candidate genes. CONCLUSION: As the two mutated genes are located on different chromosomes and cause different cancer syndromes these findings had a tremendous impact not only on genetic counseling of the index patient and her family but also on subsequent surveillance strategies.